Implementasi Kurikulum 2013 Pada Mata Pelajaran IPS Di SMP Negeri 8 Singaraja - Widiantari, Luh Putu Yuni; Irwansyah, M. Rudi (Jurnal Pendidikan Ekonomi Undiksha, 2021)
The 2013 curriculum was developed with the aim of being able to be used as a reference in the process of improving the quality of learning in schools involving teachers and students. This research is a descriptive study that aims to analyze and describe the implementation of the 2013 curriculum in social studies subjects at SMP Negeri 8 Singaraja. In line with the online learning method in the Covid-19 pandemic situation, this study observes the learning process that is organized online by paying attention to the important aspects involved in the process. The methods used in data collection are interviews, observation and documentation. While the data analysis techniques used are Data Reduction, Data Display, and Conclusion Drawing / Verification. This research shows the results that the implementation of the 2013 curriculum during the COVID-19 pandemic is related to the competency standards of graduates that have been assessed indirectly through an online learning mechanism. Content standards are carried out in scientific learning through social media platforms by providing subject matter to make students active and able to think scientifically. Process standards are seen from the activeness and ability of students to understand the material that has been taught. And the standard of assessment is seen from active participation during online learning.